Comparative study of forest biomass and carbon stocks of Margalla Hills National Park, Pakistan - Mohammad Qasim; Elmar Csaplovics (Forest Science and Technology, 2023)
AbstractForests can play an important role in climate change mitigation. However, limited information is available worldwide regarding forest carbon and biomass stocks. Financial mechanisms such as ‘reducing emissions from deforestation and forest degradation and the role of conservation of forest carbon, sustainable management of forests and enhancement of forest carbon stocks’ (REDD+) also emphasize the quantification of forest biomass and carbon. This study aimed to estimate the forest biomass in two forests of Margalla Hills National Park (MHNP): Sub-tropical Chir Pine Forest (SCPF) and Sub-tropical Broadleaved Evergreen Forest (SBEF). For this, circular sampling plots of a 20 m radius were used for the collection of the variables, “diameter at breast height (DBH) and height”. Statistical analysis was done for exploring regression relationships between the variables. We found a mean Aboveground Carbon (AGC) of 73.36 ± 32.55 Mg C ha−1 in SCPF and a mean AGC of 16.88 ± 25.81 Mg C ha−1 in SBEF. The mean Aboveground Biomass (AGB) for SCPF was recorded as 146.73 ± 65.11 Mg ha−1, while for SBEF it was 33.77 ± 51.63 Mg ha−1. It was therefore concluded that the SCPF had higher mean AGB and mean AGC than the SBEF. Similar differences were also noticed in the structural characteristics of the two forests. These could be valuable information while designing sustainable management plans and afforestation programmes for the future and also for accessing nature-based funding such as REDD+.